Clinical Correlation between Symptoms and Risk Factors with Cardiac Arrhythmias on 24-Hour Holter Monitoring - Shrestha, Hemant; Chhetriq, Surendra Bahadur; Bashyal, Bibhav; Bastakoti, Sudip; Gajurel, Ratna Mani (Journal of Institute of Medicine Nepal, 2025)
Introduction Ambulatory ECG Holter monitoring is necessary for the diagnosis of intermittent arrhythmias. The study aimed to study the clinical profile of symptomatic patients and association between symptoms and risk factors with specific arrhythmia. Methods This was a prospective observational study conducted to study the clinical profile of symptomatic patients who presented with unexplained palpitation, dizziness, syncope, or unexplained neurological events and who underwent 24-hour Holter monitoring for suspected cardiac arrhythmias. Results Overall, 265 patients were enrolled, of which 127 (47.9%) were male and 138 (52.1%) were female. The mean age of the study population was 55.5 ± 16.7. The most common indication was palpitation (58.5%), followed by dizziness (20%), unexplained neurological events (10.2%), and syncope (9.1%). The most common finding was Ventrical premature contractions (VPCs) seen in 195 (73.6%), followed by Atrial premature contractions (APCs) in 176 (66.4%), Supravenricular tachycardias (SVTs) in 33 (12.5%), and ventricular arrhythmias in 7 (2.6%). Sinus bradycardia was seen in 6 (2.3%), while sinus pause was seen in 10 (3.8%) patients. SVTs significatntly presented with palpitation (p-0.008) while sinus pause and sinus bradycardia presented with syncope (p-<0.001). Sinus pause was exclusively associated with syncope in all 10 patients (100 %). Conclusion Increasing age, smoking, hypertension, and pre-existing cardiac disease were significantly associated with abnormal Holter reports. Syncope was the only symptom that was associated with a higher prevalence of clinically significant arrhythmias. Only supraventricular tachycardias, sinus bradycardia, and sinus pause were associated with specific symptoms.